2016
DOI: 10.1016/j.jvs.2015.04.385
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous vascularization of the femoral triangle in respect to groin incisions

Abstract: The classic incisions could disrupt the cutaneous blood supply and thus increase the risk of tissue necrosis around the wound, explaining the observed postsurgical complications and infections. We propose to lower the vertical incision to start 2 cm under the inguinal ligament to reduce lesions of the cutaneous arteries and the potential devascularization of the wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
(15 reference statements)
1
10
0
Order By: Relevance
“…Thus, at least one arterial branch originated from the femoral artery and headed toward the lateral part of the thigh between the level of the inguinal ligament and the first bifurcation of the femoral artery in 94 of 100 (94%) femoral triangles. Overall, the DCIA located around the inguinal ligament and the SCIA were usually identified about 2 cm distal to the inguinal ligament ( (Tremblay et al, 2016). The external diameters of the SCIA and DCIA at their origin were approximately 2 and 3 mm, respectively ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, at least one arterial branch originated from the femoral artery and headed toward the lateral part of the thigh between the level of the inguinal ligament and the first bifurcation of the femoral artery in 94 of 100 (94%) femoral triangles. Overall, the DCIA located around the inguinal ligament and the SCIA were usually identified about 2 cm distal to the inguinal ligament ( (Tremblay et al, 2016). The external diameters of the SCIA and DCIA at their origin were approximately 2 and 3 mm, respectively ( Table 5).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the DCIA located around the inguinal ligament and the SCIA were usually identified about 2 cm distal to the inguinal ligament (Table , Figs. and ) (Tremblay et al, ). The external diameters of the SCIA and DCIA at their origin were approximately 2 and 3 mm, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significantly reduced rate of cellulitis [18], wound dehiscence, and chronic lymph edema was found, and among other things it was shown that ligation of great saphenous vein did not significantly impact the development of mentioned complications, including the limb lymphedema formation, even on long-term follow-up [19]. In terms of vascular anatomy, as suggested by other authors, the vertical incision of the region should be placed 2 cm distal to the inguinal ligament to maintain the vascular supply, when possible, in order to prevent the tissue devascularization and consequent tissue necrosis [20].…”
Section: Discussionmentioning
confidence: 97%